Predictors of functional outcome in patients with stroke thrombolysis in a tertiary hospital in Malaysia - Tai, Mei Ling Sharon; Goh, Khean Jin; Abd Kadir, Khairul Azmi; Zakaria, Mohd Idzwan; Yap, Jun Fai; Tan, Kay Sin (Stamford Publishing Pte Ltd / Singapore Medical Association, 2019)
INTRODUCTION Intravenous (IV) thrombolysis with alteplase (rt-PA) is effective in ischaemic stroke. The primary objective was to evaluate predictors of functional outcome in acute ischaemic stroke (AIS) patients treated with IV rt-PA. The secondary objective was to assess the outcome with the modified Rankin scale (mRS). We also examined the predictive value of the Totaled Health Risks in Vascular Events (THRIVE) score. METHODS AIS patients treated with IV rt-PA from February 2012 to August 2016 were recruited. Demographic data, National Institutes of Health Stroke Scale (NIHSS) scores, timing and neuroradiological findings were recorded. Patients received a dose of 0.9 mg/kg IV rt-PA within 4.5 hours of symptom onset. mRS score was evaluated at discharge and three months, and good and poor clinical outcomes were defined as scores of 0–2 and 3–6, respectively. Baseline THRIVE scores were assessed. RESULTS 36 patients received IV rt-PA. 20 (55.6%) patients had an mRS score of 0–2 at three months. Based on THRIVE score, 86.1% had a good or moderately good prognosis. On univariate analysis, poor outcome was associated with NIHSS score before rt-PA (p = 0.03), THRIVE score (p = 0.02), stroke subtype (p = 0.049) and diabetes mellitus (DM; p = 0.06). Multiple logistic regression showed that outcome was significantly associated with NIHSS score before rt-PA (p = 0.032) and DM (p = 0.010). CONCLUSION Our newly developed Malaysian IV rt-PA service is safe, with similar outcomes to the published literature. Functional outcome after thrombolysis was associated with baseline NIHSS score and DM. © 2019, Singapore Medical Association. All rights reserved.